Investigating Google Translation App Reliance on Enhancing EFL Learners’ Language Proficiency - Suleimana, Ali Ahmed; Ibrahim, Intisar Zakariya Ahmed; Yahya, Imadeldin Omer Ahmed (International Journal of Language and Literary Studies, 2025)
This study focuses on the impact of Google Translate (GTA) on EFL learners' language proficiency, specifically its advantages and disadvantages. The survey data and literature review revealed that while many learners are frequent users of GTA, particularly for vocabulary (median=4.0) and pronunciation (median=4.0), the correlations to improvement were substantial for vocabulary (?=0.72) and pronunciation (?=0.68). However, the correlations for writing (?=0.28) and comprehension (?=0.45) were weaker, suggesting limited contributions to the more complex skills of writing and comprehension. These findings also suggest that GTA may contribute to immediate improvement in vocabulary and pronunciation, but in terms of complex skills, the direct relationship between GTAs and improvement will be influenced by other contextual factors in EFL learning situations. This study emphasizes the immediate contributions to vocabulary and pronunciation while also highlighting the complexities and subtleties of incorporating GTA into language teaching and learning.